Biofortification of fruits for improved nutritional and postharvest quality - Mir, Hidayatullah; Singh, Preeti; Homa, Fozia (Journal of Postharvest Technology, 2015)
Deficiency of micronutrients and vitamins in human body can  lead to diseases, disabilities, stunted physical and mental growth.  Biofortification of food crops can be a solution for overcoming  problems of malnutrition and hidden hunger. Biofortification is  the process of increasing deficient micronutrients in the desirable  plant parts through fertilization, breeding and transgenic  approach. It is a cost-effective and sustainable approach to  provide nutrition to the under-privileged population. Other than  biofortification of staple food crops, fruit crops can also be  targeted. Fruits are already rich in health promoting substances  like vitamins, minerals and antioxidants which are required for  proper functioning of human body. Fruits like banana, strawberry,  apple, mango, etc. have been biofortified adopting various  techniques. The two challenges that are faced in the process of  biofortification of fruits are the development of nutrient rich  variety and adoption of improved variety by the farmers.
Keywords: Fruit; Biofortification; Malnutrition; Postharvest